Does Ethics Presuppose Religion? A Levinasian Perspective: Apakah Etika Mengandaikan Agama? Perspektif Emmanuel Levinas - Tjaya, Thomas Hidya (STF Driyarkara - Diskursus, 2024)
Levinas’s fundamental thought about ethics as the questioning of the I by the other earns him a unique position among moral philosophers who usually analyze the good-and-bad principles of a moral action. Levinas places such questioning on the idea of metaphysics as desire for the InÞnite that leads to the responsibility for the Other. With such an idea about ethics, one may ask whether Levinas’s thought is rooted in religion. This article purports to analyze the question by analyzing how Levinas understands the relationship between ethics and religion and whether his ethics is nothing but religion. Using the phenomenological method and textual analysis, the author shows that the answer to these questions is inherently complex. For Levinas, true ethics is fundamentally religious, and conversely, a true religion is fundamentally ethical. All this is manifested, among others, in the acknowledgment of the transcendence of the Other and the refusal to all forms of totalization. Abstrak Pemikiran fundamental Levinas mengenai etika sebagai pemertanyaan atas sang Aku oleh Yang Lain menempatkannya pada posisi unik di kalangan Þlsuf moral yang biasanya membahas prinsip baik-buruk sebuah tindakan moral. Levinas menempatkan pemertanyaan ini pada gagasan metaÞsika seperti hasrat terhadap Yang Tak Terbatas yang membawa kepada rasa tanggung jawab terhadap orang lain. Gagasan demikian dengan mudah menimbulkan pertanyaan apakah etika Levinas berakar pada agama. Artikel ini hendak menjawab pertanyaan tersebut dengan mendalami bagaimana Levinas memahami hubungan antara etika dan agama serta apakah etikanya tak lain merupakan sebuah agama. Menggunakan metode fenomenologi dan analisis tekstual, penulis menunjukkan bahwa jawaban atas pertanyaan tersebut secara inheren bersifat sangat kompleks. Bagi Levinas, etika sejati secara fundamental bersifat religius, dan demikian pula, agama sejati secara fundamental bersifat etis. Hal ini terungkap antara lain dalam pengakuan atas transendensi Yang Lain dan penolakan atas segala bentuk totalisasi. Kata-kata Kunci: etika, agama, transendensi, Yang Lain, totalisasi, Yang Tak Terbatas.